Building Blocks of Structural Intervention: A Novel Modular Paradigm for Procedural Training. (October 2017) - Raphael, Claire E.; Alkhouli, Mohamad; Maor, Elad; Panaich, Sidakpal S.; Alli, Oluseun; Coylewright, Megan; Reeder, Guy S.; Sandhu, Gurpreet; Holmes, David R.; Nishimura, Rick; Malouf, Joseph; Cabalka, Allison; et al.
Abstract : Structural heart disease is a rapidly evolving field, and approaches to procedural training are not standardized. We describe a novel modular approach to procedural training that considers each procedure as a series of building blocks that may be taught and assessed separately. Ten key structural heart disease building blocks can be identified, which, when combined with the cognitive skills of structural intervention and device-specific training, allow appropriate planning and implementation of structural procedures. Structural procedures require careful navigation of the aorta, left atrium, and right heart, including detailed understanding of relational anatomy. Component blocks include large bore vascular access, navigation within the left atrium, occlusion, snaring, and 3-dimensional relational anatomy. These building blocks also provide the foundation for new procedures through innovative use of the skill sets and devices to approach new clinical problems. The addition of device-specific training may be provided via proctoring and industry support. Using this approach, competency in less common procedures may be achieved and maintained. We discuss each building block in detail, approaches specific to the structural heart disease patient, the need for cross-discipline training, and empirical recommendations for training using this approach. We postulate that this new paradigm may be the preferred approach for training and assessment of structural heart disease interventional skills.